Efficient Simulation of the Outage Probability of Multihop Systems - Chaouki Ben Issaid; Mohamed-Slim Alouini; Raul Tempone (IEEE Photonics Journal)
In this paper, we present an efficient importance sampling estimator for the evaluation of the outage probability of multihop systems with amplify-and-forward channel state-information-assisted. The proposed estimator is endowed with the bounded relative error property. Simulation results show a significant reduction in terms of number of simulation runs compared to naive Monte Carlo.